O TEATRO DE FORMAS ANIMADAS NA EDUCAÇÃO NÃO-FORMAL: AÇÕES ESPECÍFICAS COM BONECOS E SOMBRAS. - REIS FILHO, Raimundo Barbosa (2018)
This work aims to reflect on the experience as a teacher of Theater of Animated Forms, acting voluntarily at the Centro Cultural e Educacional da Vila Embratel, a neighborhood located on the outskirts of the city of São Luís, capital of the State of Maranhão. The reflections described here deal with the activities developed outside the formal classroom, with students and teachers of the institution, as well as with some young people of the community, using techniques of Puppet Theater and Shadow Theater, aiming at educational possibilities and / or artistic, focused on the daily life of those agents.